Quantification and benefits of reducing post-harvest losses: Evidence for vegetables in Senegal - Beye, Assane; Komarek, Adam M. (University of Bonn, 2020)
This study examines on-farm post-harvest losses (PHL) for three vegetable crops (onion, tomato, and pimento) in Senegal and the potential economic benefits associated with reducing PHL for these three vegetables. Household survey data was used to quantify the on-farm PHL for these vegetables at different stages between the crop’s harvest and the sale or consumption. A multi-market model was used to simulate the effect of eliminating vegetable PHL on the total value of vegetable supply and international trade of vegetables at the national level. Results suggest that on average 30% of vegetable production is lost on-farm and is therefore unavailable for sale or consumption. Eliminating these losses could increase the total value of vegetable supply by 45% (US $72 million) per year and reduce vegetable imports by 22% (127,000 tons) per year. Moreover, our results indicate that both private costs to farmers and public costs to the government related to such PHL reductions would need due consideration when prioritizing between investments in the agricultural sector and beyond.